THE COST OF UNIFORMITY: THE CASE OF STATE SCHOOL STUDY TOUR FROM ANTI CORRUPTION PERSPECTIVE - Alamsyah, Aam; Radik Darmawan,; Santosa, Santosa (Journal of Innovation Research and Knowledge, 2024)
Scientific traveling, frequently called a study tour, is a regularly conducted program by school management and must be followed by the school students regardless of their parent's financial condition. This event must be followed in order for the students to be able to do some scientific projects. Even though some school managements do not force all students to participate in this program, most of the school students feel obligated to participate. The study tour has been prominently discussed and reported due to the numerous impacts of this program. It persists due to potentially beneficial factors, such as the possible income reaching hundreds of millions and becoming a financial source for school management and other related parties (bus providers, travel agents, hotel providers). Even though the government fully funds the state school, the need for more cash and funds makes the school management hold the event regularly. Of the government's objective to create a freedom to learn and a free-from-corruption education program, the culture of forcing students to participate in the so-called study tour should be prohibited. Furthermore, the implementation of this program should be tightly supervised so that potential maladministration can be prevented. In sum, such expensive traveling camouflaged with the name scientific activities can also be conducted in much more affordable programs, for instance, by choosing the nearest colleges/universities, reducing the length of programs, and choosing the most relevant institutions to the students' diversified interests and future career prospects.